Dinamika neposredne delavske participacije - Franca, Valentina (Podjetje in delo, 2025)
The article comprehensively addresses direct employee participation as a crucial yet complex topic within contemporary industrial relations, with a focus on the European context. It explores various forms of direct employee participation, from team-based decision-making to job autonomy and suggestion systems, and analyses how these practices evolve through different “escalators of participation” - from basic information sharing to co-determination and control. The main findings indicate that the effectiveness of direct employee participation is not universal; rather, it is highly dependent on contextual factors such as organizational culture, leadership style, and the structural position of workers. The author emphasizes that direct employee participation is an important tool for improving job quality, fostering innovation, enabling effective digital transformation, and achieving sustainability goals. However, it also warns of potential risks, such as work intensification and the “voice gap.” A key finding is also that direct participation functions best in a complementary relationship with indirect, representative participation (trade unions, works councils), as their synergy yields the best results. The case of Slovenia highlights the specific nature of its legal framework, which allows for a high degree of participation, but in practice faces challenges, especially in the public sector and due to a lack of systemic mechanisms and awareness. In short, the future of effective employee participation depends on the system’s ability to adapt to new challenges, such as digitalization and new forms of work, and the integration of all voice channels to ensure meaningful involvement of all employees.
Keywords: delavci; indirect employee participation; industrial relation; industrijska razmerja; job quality; kakovost delovnih mest; neposredna delavska participacija; sindikati; trade unions; workers